(untitled) (UNED Research Journal, 2017)
From its beginings, the Distance State University of Costa Rica has offered presential tutoring as a support tool for students. However, the use of virtual platforms is increasing at the Agroindustry Chair, and to determine whether presential tutoring is still considered necessary by the students, as well as wanted characteristics and opinion on evaluative activities. Students suggested that undergraduate courses need more presential tutoring than advanced courses (p=0,003). On the other hand, alternative evaluative activities are preferred to written tests in both levels. For evaluative activities, all students would prefer collaborative work over tests.